Odpowiedzi

2010-03-03T15:50:08+01:00
A)
4x-3=3x+5
4x-3x=5+3
x=8
b)
5x+2=7-3x
5x+3x=7-2
8x=5/8
x=5/8
c)
3(x-1)=0
3x-3=0
3x=3/3
x=1
d)
-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30/(-6)
x=-5
2010-03-03T15:53:16+01:00
A) 4x-3=3x+5
4x-3x=5+3
x=8

b) 5x+2=7-3x
5x+3x= 7-2
8x= 5 /:8
x= ⅝

c)3(x-1)=0
3x-3=0
3x=3/:3
x=1

d) -6(x+1)=24
-6x-6=24
-6x= 24+6
-6x= 30/:(-6)
x= -5
2010-03-03T15:53:48+01:00
4x-3=3x+5 /-3x
x-3=5 /+3
x=8

5x+2=7-3x /+3x
8x+2=7 /-2
8x=5 /:8
x=1.6

3(x-1)=0
3x-3=0 /+3
3x=3 /:3
x=1

-6(x+1)=24
-6x-6=24 /+6
-6x=18 /: (-6)
x=3